The Impact of Over-Tourism on the Sustainability of Indigenous Peoples in Bali - Maya Poetra, Rizal Akbar; Nurjaya, I Nyoman (Universitas Semarang, 2024)
This research examines the impact of the over-tourism phenomenon on the sustainability of customary law communities in Bali Province, Indonesia. Bali, as one of the most popular tourist destinations in the world, has experienced a significant surge in the number of tourists in the last few decades. This phenomenon triggers various problems, including pressure on the environment, socio-cultural changes, and threats to the sustainability of traditional communities that have long maintained local traditions and values. This research finds that increased tourism has a negative impact on the sustainability of local ecosystems, reduces the traditional practices of indigenous communities, and threatens the local wisdom that is the basis of their cultural identity. This research highlights the need for tourism management strategies that are more sustainable and sensitive to local culture to protect the sustainability of traditional communities in Bali. Therefore, this research offers a new perspective on preserving traditional legal communities in Bali through a tourism management approach that is centered on local values, which has not been widely discussed in previous studies.